Strategic Role of Zakat in Multidimensional Quality of Life in Sijunjung, Indonesia - Hamimi, H.; Ismail, A. G.; Zaenal, M. H. (Universiti Sains Islam Malaysia, 2024)
Zakat is one of the five pillars of Islam which has a function of faith, social and economic functions. Muslims who can pay zakat are required to give at least 2.5 per cent of their wealth. The problem of poverty prevalent in disadvantaged regions because of the difficulty of access to information and communication led to a gap that is so high in wealth and resources. The instrument of zakat provides a paradigm in the achievement of equitable wealth distribution and healthy circulation. Zakat potentially offers a better life and improves the quality of human being. There is a human quality improvement not only in economic terms but also in spiritual terms such as improving religiousity. This study aims to examine the role of zakat to alleviate humanitarian issues in disadvantaged regions such as Sijunjung, one of zakat beneficiaries and impoverished areas in Indonesia. The researcher attempted a Cibest method to capture the impact of zakat beneficiaries before and after becoming a member of Zakat Community Development (ZCD) Program in material and spiritual value. The overall analysis shows that zakat has a positive impact on disadvantaged regions development and enhance the quality of life of the community. There is an improvement in the average of mustahik household incomes after becoming a member of ZCD Program. Cibest model demonstrates that material, spiritual, and absolute poverty index decreased by 10, 5, and 6 per cent. Meanwhile, the welfare index is increased by 21 per cent. These findings have significant implications for developing the quality of life in disadvantaged regions in Sijunjung. Therefore, zakat is one of the instruments to change the status of disadvantaged areas to be equivalent to other areas.